The influence of soil properties on denitrifying bacterial communities and denitrification potential in no-till production farms under contrasting management in the Argentinean Pampas - Rosa, Silvina Mariana; Behrends Kraemer, Filipe; Soria, Marcelo Abel; Guerrero, Leandro Demián; Morras, Hector; Figuerola, Eva Lucia Margarita; Erijman, Leonardo (Elsevier, 2018)
The aim of this work was to investigate the response of the structure, abundance and potential activity of denitrifiers to contrasting agricultural management in no-till production fields, across a regional scale within the highly productive Argentine northern Pampas. Treatment categories were grouped according to the sustainability of the soil management, in terms of crop rotation, fertilization, agrochemicals use and pest control, as good no-till agricultural practices (GAP) and poor no-till agricultural practices (PAP). Non-cultivated soils in each geographic location were also evaluated as reference groups. Mixed models, with sites treated as random factors, indicated that the potential denitrification activity and the size of the nirS community differed significantly between non-cultivated and PAP soils. Soil properties were separated into dynamic and inherent according to their variance components. The former had the largest part of their variances explained by agricultural management, while the latter were more affected by edaphic–climatic differences between sites. Both inherent and dynamic properties could explain the changes in potential denitrification activity, whereas changes in the abundance of denitrifiers were only related to inherent soil properties. Results from principal components analysis suggested site-specific response of most dynamic soil properties. Among the latter, only aggregate stability indices were strongly associated with potential denitrification activity after removing the geographical effect.